Supergravity and superstrings a geometric perspective - Castellani Leonardo; D'Auria Riccardo; Fre Pietro (Singapore World Scientific, 1991)
This book is divided into three volumes and six parts. The first volume introduces the geometric and algebraic foundations of supergravity. The second volume is devoted to the construction of supergravity theories limited to second order derivate interac
V1: Mathematical foundations
Keywords: Differential geometry; Supergravity; Superstring theories; Supersymmetry